The Integration of Culture and Religion: A Functional Analysis of the Rebo Bontong Tradition in the Strengthening of Social Solidarity in Memunggu Hamlet - Siti Juliati Ningsih (Tabéq Care Center and UIN Mataram, 2026)
The Rebo Bontong tradition represents a form of local wisdom among the Sasak people, embodying social, cultural, and spiritual values transmitted across generations. Despite the pressures of modernisation, the Memunggu Hamlet community continues to preserve this tradition. This study analyses the practice of the Rebo Bontong tradition and its impact on social cohesion and solidarity within the community. Employing a qualitative methodology grounded in social phenomenology and field research, data were collected through non-participatory observation, in-depth interviews with community and religious leaders, and documentation. Drawing on Talcott Parsons’ structural functionalism, the tradition persists because it fulfils four systemic prerequisite functions (AGIL): Adaptation (adjustment of the tradition to Islamic values and contemporary conditions), Goal Attainment (realisation of collective objectives such as safety and protection from misfortune), Integration (unification of residents across social strata through mutual aid and communal gatherings), and Latency (preservation of ancestral value patterns by traditional leaders for younger generations). The findings demonstrate that the Rebo Bontong tradition functions not only as a metaphysical ritual but also as an effective sociological mechanism. Its implementation strengthens social bonds, mitigates potential conflicts, fosters collective solidarity, and contributes to social stability within the community.